Influência dos ciclos térmicos e do tratamento térmico de envelhecimento nas temperaturas de transformação de ligas Cu-Al-Be-Cr - Guedes, Nilmário Galdino (2015)
Shape memory alloys are widely used to produce mechanical actuators which operate in a temperature range that are responsible for the shape recovery of the sensor element. Such applications are numerous engineering. In this case, the main aspect responsible for a good performance of the system is the stability of the characteristics temperature of the alloy, i.e., the start and finish temperatures of the austenitic and martensitic transformations. Cu-Al-Be alloys are very attractive from the commercial point of view and have low transformation temperatures, thus, attractive for various applications. However, the stability of the phases is still the subject of various investigations. In this work, a device for conducting thermal cycling experiments was constructed which is able to cycling the samples up to 10,000 times, enabling the investigation of the thermal stability of Cu-Al-Be alloy containing Cr, as grain refining element. Experimental results have shown that the thermal cycling over extended periods of times increases the temperatures of the martensitic phase reversion - stabilizing the martensite phase. On the other hand tests carried out during the aging heat treatments did not significantly alter these temperatures. It was concluded that the main mechanism for stabilization of the martensitic phase is related to the immobilization of the interface due to defects introduced during the thermocycling.